The influence of organizational culture and spiritual intelligence on employee performance through emotional intelligence - Sancoko, Reni; Setiawan, Margono; Troena, Eka Afnan (MEC-J (Management and Economics Journal), 2019)
This study aims to analyze the relationship between organizational culture, spiritual intelligence, emotional intelligence and employee performance at the PT. PLN (Persero) Distribsui Bali. The research population is employees who are permanent employees with a minimum work period of 1 year totaling 189 people. The sampling technique used was simple random sampling with the number of respondents 128 people and using SPSS 2.1 as an analytical tool. Research findings indicate that organizational culture and spiritual intelligence have a significant effect on emotional intelligence. In addition, organizational culture and spiritual intelligence have a significant effect on employee performance. And emotional intelligence has a significant influence on employee performance. This study also emphasizes that emotional intelligence mediates some of the influence of organizational culture on employee performance. And emotional intelligence mediates some of the influence of spiritual intelligence on employee performance. Finally, this study verifies that organizational culture and spiritual intelligence in private organizations are able to provide useful finding such as those found in public organizations (BUMN). This research only focuses on spiritual intelligence and emotional intelligence. Subsequent research can investigate other intelligence possessed by humans such as intelligence quotient and physical intelligence. In terms of comparing the two human intelligences with spiritual intelligence and emotional intelligence in the hope of verifying whether employees who are intellectually intelligent, physical, spiritual and emotional can greatly help the organization to improve employee performance.Â